Correlating the electronic structures of metallic/semiconducting MoTe2 interface to its atomic structures. Issue 2 (29th April 2020) - Han, Bo; Yang, Chen; Xu, Xiaolong; Li, Yuehui; Shi, Ruochen; Liu, Kaihui; Wang, Haicheng; Ye, Yu; Lu, Jing; Yu, Dapeng; Gao, Peng
Abstract: Contact interface properties are important in determining the performances of devices that are based on atomically thin two-dimensional (2D) materials, especially for those with short channels. Understanding the contact interface is therefore important to design better devices. Herein, we use scanning transmission electron microscopy, electron energy loss spectroscopy, and first-principles calculations to reveal the electronic structures within the metallic (1T ′ )-semiconducting (2H) MoTe2 coplanar phase boundary across a wide spectral range and correlate its properties to atomic structures. We find that the 2H-MoTe2 excitonic peaks cross the phase boundary into the 1T ′ phase within a range of approximately 150 nm. The 1T ′ -MoTe2 crystal field can penetrate the boundary and extend into the 2H phase by approximately two unit-cells. The plasmonic oscillations exhibit strong angle dependence, that is a red-shift of π+σ (approximately 0.3–1.2 eV) occurs within 4 nm at 1T ′ /2H-MoTe2 boundaries with large tilt angles, but there is no shift at zero-tilted boundaries. These atomic-scale measurements reveal the structure–property relationships of the 1T ′ /2H-MoTe2 boundary, providing useful information for phase boundary engineering and device development based on 2D materials. Abstract : The properties of 1T ′ /2H-MoTe2 phase boundaries are measured at atomic-scale and found to be angle-dependent, providing guidelines to tune the local band structure and contact resistance.